2023
DOI: 10.3390/nu15020363
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Situation Analysis in the UAE: A Review Study

Abstract: This review study aimed to assess the nutrition situation in the UAE using published data from 2010 to 2022. It highlights the gaps and challenges that prevail in addressing the nutrition-related problems in the UAE and the opportunities that have been overlooked. The available literature indicates that the UAE is burdened with more than one form of nutrition-related problems, including being underweight, being overweight, obesity, micronutrient deficiencies, and nutrition-related chronic diseases. It is clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…Several studies discussed the prevalence rate of exclusive breastfeeding in both the West Bank and the Gaza Strip. The prevalence in overall Palestine (43.3%) was below the WHO target prevalence and other regional countries, such as the reported prevalence in the UAE (59.7%) ( 131 ) but higher than those in Jordan (25.4%) ( 126 ) and Lebanon (27%) ( 132 ). Factors associated with low exclusive breastfeeding found in both the West Bank and the Gaza Strip include the perception that breast milk is not sufficient to meet an infant's needs, a younger maternal age, and the number of children.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Several studies discussed the prevalence rate of exclusive breastfeeding in both the West Bank and the Gaza Strip. The prevalence in overall Palestine (43.3%) was below the WHO target prevalence and other regional countries, such as the reported prevalence in the UAE (59.7%) ( 131 ) but higher than those in Jordan (25.4%) ( 126 ) and Lebanon (27%) ( 132 ). Factors associated with low exclusive breastfeeding found in both the West Bank and the Gaza Strip include the perception that breast milk is not sufficient to meet an infant's needs, a younger maternal age, and the number of children.…”
Section: Discussionmentioning
confidence: 66%
“…However, in the Gaza Strip, the percentage is still relatively high (9.7%). While the study in the West Bank has a different prevalence (13.7%), this rate was below the global level (14.6%) ( 123 ), not far from Western Asia (10.9%) ( 124 ) but not less than that in the UAE (11.8%) ( 125 ), and Jordan (16.7%) ( 126 ). Factors discussed in the studies were smoking, anemia, a high number of parities, and diet during pregnancy.…”
Section: Discussionmentioning
confidence: 89%
“…One of the major concerns for child health in the UAE is malnutrition (Al Sabbah et al, 2023;Galal & Hulett, 2023;Cheikh Ismail et al, 2022;Nasreddine et al, 2018). According to Nassreddine et al, (2022), in UAE, 10% children among 0-4 years old were stunting.…”
Section: Why Child Health Is a Concern In Uae?mentioning
confidence: 99%
“…According to Nassreddine et al, (2022), in UAE, 10% children among 0-4 years old were stunting. On the other hand, Al Sabbah et al, (2023) reported that according to UNICEF, the rate of low birth weight in the UAE increased from 6.9% in 2000 to 11.6% in 2015. The UAE Ministry of Health also reported a similar rate of 11.8% in 2019, while a study in Abu Dhabi found a rate of 9.4% in 2020.…”
Section: Why Child Health Is a Concern In Uae?mentioning
confidence: 99%
See 1 more Smart Citation